Suppression of kinesin family member-18A diminishes progression and induces apoptotic cell death of gemcitabine-resistant cholangiocarcinoma cells by modulating PI3K/Akt/mTOR and NF-κB pathways - Pakornkiat Tanasuka; Phonpilas Thongpon; Sasitorn Chomwong; Suppakrit Kongsintaweesuk; Somchai Pinlaor; Thatsanapong Pongking; Sasithorn Watcharadetwittaya; Chawalit Pairojkul; Kitti Intuyod (PLoS ONE, 2025)
Cholangiocarcinoma (CCA), particularly when associated with Opisthorchis viverrini infection, is often diagnosed at a late stage and exhibits high resistance to chemotherapy, notably gemcitabine. While kinesin family member 18A (KIF18A) is upregulated in opisthorchiasis-associated CCA, its precise function, especially in gemcitabine-resistant CCA, remains largely unexplored. Herein, expression of KIF18A in relation to survival and progression was assayed by TCGA database mining and immunohistochemistry of a tissue microarray derived from 84 CCA patients. For functional study, KIF18A was suppressed in gemcitabine-resistant CCA cells (KKU-213BGemR) using a CRISPR/Cas9 technique, followed by cellular and molecular analyses. Our results showed that KIF18A was highly expressed in CCA tissues compared to normal counterparts. Its expression was significantly correlated with tumor size and histological type of CCA but not with overall survival time. In vitro, KIF18A expression levels were increased in CCA cell lines, particularly KKU-213BGemR. Suppression of KIF18A significantly inhibited colony formation, migration and invasion by KKU-213BGemR cells. In addition, KIF18A knockdown led to a significant increase in the sub-G1 population, indicating the occurrence of cellular apoptosis. Flow cytometry confirmed that suppression of KIF18A significantly induced early apoptotic cell death of KKU-213BGemR cells. Suppression of KIF18A dramatically downregulated the expression of key oncogenic and survival signaling proteins, including PI3K (total and p-PI3K), Akt (total and p-Akt), mTOR (total and p-mTOR), NF-κB (total and p-NF-κB) and Bcl-2 in KKU-213BGemR cells. Taken together, our findings suggest that KIF18A plays crucial roles in promoting the progression and survival of gemcitabine-resistant CCA cells, partly by modulating PI3K/Akt/mTOR and NF-κB pathways. Therefore, despite its lack of prognostic utility, KIF18A represents a promising therapeutic target for improving treatment outcomes in CCA patients, especially those who do not respond to gemcitabine treatment.